A review on sustainable wellbeing indicators for human interrelationships with the environment - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Zen, Ismawi; Abdullah, Muhammad Faris (Malaysian Institute of Planners, 2017)
The environment should appear not only as a commodity to humans but as an inspiring source that appeals to humans’ ethical ability. In Malaysia, studies concerning factors influencing pro-environmental behaviours are vast. However, studies on interrelationships between humans and the contextual surroundings are scarce. Towards achieving sustainable well-being, it is undoubtedly important for humans to have conforming emotions, behaviours, cognitions and motivations towards the environment. This study intends to identify the determinants of human values and ethical behaviour concerning the environment towards developing a theoretical framework of interrelationship between human and environment.